2016
DOI: 10.18632/oncotarget.13639
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity of metformin: from metabolic and epigenetic perspectives

Abstract: Metformin has been used to treat type 2 diabetes for over 50 years. Epidemiological, preclinical and clinical studies suggest that metformin treatment reduces cancer incidence in diabetes patients. Due to its potential as an anti-cancer agent and its low cost, metformin has gained intense research interest. Its traditional anti-cancer mechanisms involve both indirect and direct insulin-dependent pathways. Here, we discussed the anti-tumor mechanism of metformin from the aspects of cell metabolism and epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 59 publications
0
49
0
2
Order By: Relevance
“…In the past decade, many epidemiological studies showed the association between metformin use and the reduced risk and improved survival of patients with several types of cancers, including gynecological cancers. The beneficial effects of metformin use on EC may depend on common anticancer mechanisms present in other gynecological cancers [33] and even all tumors [34], but the exact molecular mechanism has not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, many epidemiological studies showed the association between metformin use and the reduced risk and improved survival of patients with several types of cancers, including gynecological cancers. The beneficial effects of metformin use on EC may depend on common anticancer mechanisms present in other gynecological cancers [33] and even all tumors [34], but the exact molecular mechanism has not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…While aerobic glycolysis is a known feature of cancer cells, targeting this pathway for therapy has proven challenging due to the cytotoxicity of many anti-glycolytic agents [25]. Biguanides, such as metformin and phenformin, are common therapeutics for the treatment of type 2 diabetes, and have recently been reported to exhibit anticancer activity in vitro and in vivo [26][27][28]. Specifically, both agents have an inhibitory effect on glycolysis and oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review based on 179 trials and 25 observational studies, the use of metformin as monotherapy or in combination as first-line treatment of hyperglycemia has been strongly recommended, given its relative safety and beneficial effects on hemoglobin A1c, weight, and cardiovascular mortality (compared with sulfonylureas) (28). Furthermore, metformin has been extensively studied to suppress tumorigenesis by direct and indirect mechanisms (29).…”
Section: How Do We Manage Hyperglycemia In Diabetic Patient With Ckd?mentioning
confidence: 99%